2020
DOI: 10.31234/osf.io/cxp8n
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge, attitudes, and practices towards measures for prevention of the spread of COVID-19: An online cross-sectional survey among Bangladeshi residents

Abstract: The novel coronavirus (SARS-CoV-2/ COVID-19) rapidly infects people across the world, leading to a massive public reaction. Peoples’ knowledge, attitudes, and practices (KAP) towards measures for prevention of the spread of COVID-19 are the most important for the control and prevention of the pandemic infectious disease. This study aimed to assess the knowledge, attitude & practices (KAP) towards measures for prevention of the spread of COVID-19 among Bangladeshi residents during the COVID-19 pandem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 17 publications
4
2
0
Order By: Relevance
“…On average, participants had a 74.5% practice score and 55% participants had more frequent practice, which was consistent with some studies from Bangladesh (6,7,9,25). So, our study indicates that the preventive practice level remains similar to what was in last year.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…On average, participants had a 74.5% practice score and 55% participants had more frequent practice, which was consistent with some studies from Bangladesh (6,7,9,25). So, our study indicates that the preventive practice level remains similar to what was in last year.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings suggested that Bangladeshi adults might have lost their confidence towards controlling the rapid escalation of coronavirus as only 34.6% of participants took it confidently that Bangladesh can win the battle against covid-19 and concomitantly, only 43.8% of participants were confident that covid-19 will finally be controlled. Last year, Rabbani et al, (2020) reported that 55.3% of their participants were confident as to Bangladesh would win the battle against covid-19 which was also consistent with Kundu et al, n.d. (2020), and 68.5% were confident that covid-19 would be finally controlled which was somewhat lower compared to Banik et al, (2020) (8,9,25). On the other hand, a Malaysian, Chinese, Saudi Arabian, Indonesian, Nepali article published last year (2020) reported that they respectively obtained 83.1%, 90.8%, 94%, 94.3%, and 71.5% positive responses regarding whether covid-19 would successfully be controlled, and 95.9%, 97.1%, 97%, 95.5%, and 80% positive response regarding whether their country would be able to win the battle against covid-19 (18– 20,23,26).On the whole, it is obtrusive that attitude level among the populace has noticeably subsided.…”
Section: Discussionmentioning
confidence: 69%
“…On average, participants had 74.2% of total practice score and 55% of participants had more frequent practice of Covid-19 preventive measures (CPM), which is consistent with some earlier studies from Bangladesh [ 4 , 6 , 7 , 23 ]. Thus, our findings indicate that the preventive practice level remains similar to what was in last year.…”
Section: Discussionsupporting
confidence: 89%
“…Our findings indicated that Bangladeshi students might have lost their confidence toward controlling the rapid escalation of coronavirus as only 35.3% of participants were confident in believing that Bangladesh could win the battle against Covid-19 and concomitantly, only 44.2% of participants were confident that Covid-19 would finally be controlled. Rabbani et al [8] reported that 55.3% of their participants were confident about that Bangladesh would win the battle against Covid-19 which is also consistent with Kundu et al [23], and 68.5% were confident that Covid-19 would finally be controlled which is somewhat lower compared to Banik et al [7]. On the other hand, Malaysian, Chinese, Saudi Arabian, Indonesian, Nepali studies obtained, respectively, 83%, 91%, 94%, 94%, and 71.5% positive responses regarding whether Covid-19 would successfully be controlled, and 96%, 97%, 97%, 95.5%, and 80% positive response regarding whether their country would be able to win the battle against Covid-19 [16-18, 21, 24].…”
Section: Plos Onesupporting
confidence: 72%
“…Evidence suggested that the rate of washing hand increased significantly (88.4%) after the coronavirus invasion and on average they wash their hands three times per day [30]- [32]. Some study also found that by using the nationwide representative data, more than ¾ people wash their hand after coming back from outsides [30], [33]. But after sneezing, coughing the rate of washing hand is comparatively low (about 37%) [30].…”
Section: Hand Washing Practicesmentioning
confidence: 99%